INFLUENCE OF LOGISTICS INFORMATION SYSTEM MANAGEMENT ON PERFORMANCE OF FOOD AND BEVERAGE MANUFACTURING FIRMS IN KENYA - Jepchumba, Naomy; Ngugi, Patrick Karanja; Shale, Noor Ismail (Machakos University Press, 2021)
The purpose of this paper is to assess the influence of logistics information systems management on the performance of food and beverage manufacturing firms in Kenya. Manufacturing companies in Kenya have been experiencing problems in the performance of their production and operations management. In view of the foregoing, it is relevant to investigate how Kenyan organizations could outsource their logistics requirements through logistics information systems management in the most efficient manner with regard to customer service and cost. In Kenya, studies have reported mixed findings with regard to logistics information systems management and its influence on firm performance among food and beverage manufacturing firms, while published literature on logistics information systems management and firm performance lacks in the country. It is against this backdrop that the present study sets out to investigate the influence of logistics information systems management on performance of food and beverage manufacturing firms in Kenya. This research study adopted a descriptive research design approach. Data was collected using self-administered questionnaires. The data collected was analyzed by use of descriptive and inferential statistics. Multiple regression model was used to show the relationship between the dependent variable and the independent variables. The findings from the study revealed that logistics information systems management had a significant influence on the performance of food and beverage processing firms. Policy and governance framework was also found to significantly moderate the relationship between logistics information systems management and performance of food and beverage processing firms. The study concluded that logistics information system management was critical in enhancing the performance of food and beverage processing firms in Kenya. The study recommends that the management of food and beverage processing firms ought to embrace enhanced use of logistics information systems to enhance performance.
Keywords: Logistics Information System Management; Fourth Party Logistics; Food and Beverage Manufacturing Firms; Firm Performance